КОМПОСТУВАННЯ ОРГАНІЧНОЇ РЕЧОВИНИ. МІКРОБІОЛОГІЧНІ АСПЕКТИ - Гаценко, М. В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2014)
The following literature review describes various methods of organic matter composting, dominant trends in different historical periods, advantages and disadvantages of the existing composting methods, modern technologies of vermicomposting and enriching of composts.